PROFIL BERPIKIR KRITIS MAHASISWA DALAM MEMECAHKAN MASALAH GEOMETRI DITINJAU DARI ADVERSITY QUOTIENT DAN LEARNING STYLE - Agustina Mei; Sofia Sa'o; Finsensius Yesekiel Naja (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Each individual can think critically in solving problems according to the differences in their adversity quotient and learning style. This study aims to describe the critical thinking profile of mathematics students who have visual, auditory, kinesthetic learning styles and adversity quotient climbers in solving geometry problems. This research is a descriptive study using a qualitative approach. The research subjects were students of mathematics education at the University of Flores. The instruments in this study were the researchers themselves, adversity quotient questionnaires, learning style questionnaires, and Problem Solving Tests. The results obtained are that 1) Subjects with visual learning style and adversity quotient climbers in solving problems can understand the problems at hand, can plan and can carry out the completion process well, and re-examine the work. 2) Subjects with auditory learning style and adversity quotient climbers can understand the problem given, do not plan so that the implementation is not detailed, re-examine the work. 3) Subjects with kinesthetic learning style and adversity quotient climbers can understand the problem, plan but the subject solves it directly, does not re-examine what has been done. It was concluded that each individual has a different way of understanding and solving problems.